2011
DOI: 10.1371/journal.pone.0015879
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Induced Metastatic Modulators MMP-2 and MMP-9 Are Targets of 3,3′-Diindolylmethane in Thyroid Cancer

Abstract: BackgroundThyroid cancer is the most common endocrine related cancer with increasing incidences during the past five years. Current treatments for thyroid cancer, such as surgery or radioactive iodine therapy, often require patients to be on lifelong thyroid hormone replacement therapy and given the significant recurrence rates of thyroid cancer, new preventive modalities are needed. The present study investigates the property of a natural dietary compound found in cruciferous vegetables, 3,3′-diindolylmethane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 46 publications
2
55
0
Order By: Relevance
“…Epidemiologic studies suggest MMP-2 quantification as prognostic marker in patients with colorectal cancer, ovarian cancer and thyroid cancer (Kwon et al, 2011;Rajoria et al, 2011). Up-regulated levels of gelatinase A are observed in patients with breast, gastric, bone and melanoma tumors (Daniele et al, 2010;Gerstein et al, 2009;Kushlinsky et al, 2010;Nikkola et al, 2005;Ranogajec et al, in press;Stankovic et al, 2010).…”
Section: Biological Aspectsmentioning
confidence: 99%
“…Epidemiologic studies suggest MMP-2 quantification as prognostic marker in patients with colorectal cancer, ovarian cancer and thyroid cancer (Kwon et al, 2011;Rajoria et al, 2011). Up-regulated levels of gelatinase A are observed in patients with breast, gastric, bone and melanoma tumors (Daniele et al, 2010;Gerstein et al, 2009;Kushlinsky et al, 2010;Nikkola et al, 2005;Ranogajec et al, in press;Stankovic et al, 2010).…”
Section: Biological Aspectsmentioning
confidence: 99%
“…Finally, MMP2 was considered as a potential tumor marker to identify greater risk of metastasis (Liang et al, 2011). Moreover, MMPs are known to promote tumor metastasis and are determined as targets of 3,3'-di indolylmethane(DIM),which is believed to have antiestrogen like property and can be considered as a potential novel preventive/therapeutic dietary supplement in thyroid cancers (Rajoria et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The cycle-dependent effects of BR-DIM on synchronized cancer cells progressing from G1 to S-phase has been reported previously (Chinnakannu et al 2009), suggesting that BR-DIM induces p27 Kip1 -another CDK inhibitor in these cells. Substantial evidence indicates the role of DIM in modulating other crucial G1-acting cell cycle components in human cancer cell lines (Garikapaty et al 2006;Rajoria et al 2011). Included among these components are CDK4, CDK6 and cyclin D. It is also noteworthy that DIM diminishes the levels of cyclin A and D1 along with the activity of CDK4, CDC2, and CDC25C phosphatase, causing a "brake" in cell cycle progression (Choi et al 2009).…”
Section: Dim and Cell Cyclementioning
confidence: 99%
“…It has been shown that DIM down-regulates uPA-uPAR leading to reduced production of VEGF/MMP-9 which led to the inhibition of cell growth, migration and aggressiveness of prostate and breast cancer cells (Ahmad et al 2009a, b), suggesting the importance of uPA/uPAR in BR-DIM-mediated regulation of cancer cell growth and migration. Other metastatic regulators, including proteolytic enzymes MMP-2 and MMP-9 have been reported to be inhibited by DIM (Rajoria et al 2011). DIM has also been reported to be potentially effective in inhibiting growth and invasion of drug resistant human cancer cells from breast, glioma and non-small cell lung cancer expressing EGFR mutant (Rahimi et al 2010).…”
Section: The Role Of Dim In Invasion and Metastasismentioning
confidence: 99%